Phytoremediation of Copper‐Contaminated Soil Using Helianthus annuus, Brassica nigra, and Lycopersicon esculentum Mill.: A Pot Scale Study. Issue 4 (June 2016) - Lothe, Anjali G.; Hansda, Arti; Kumar, Vipin
Abstract : Phytoremediation is an eco‐friendly and cost‐effective technology that uses plants to extract contaminants from the environment or to decrease contaminant toxicity. This article documents a study not only of the effectiveness of copper uptake by Heliantus annuus (common sunflower), Brassica nigra (black mustard), and Lycoperscion esculentum Mill. (a tomato species), but of where, within these plant species, the copper is accumulated—in the roots or in the shoots. This is vital information, for if these particular plants accumulate copper primarily in their roots, then their edible portions will likely be safe to eat, while if they accumulate the copper in their shoots, their harvestable portions would be harmful to living beings.